Extent of Neck Dissection and Cervical Lymph Node Involvement in Oral Squamous Cell Carcinoma - Thoenissen, Philipp; Heselich, Anja; Deeg, Stefanie; Al-Maawi, Sarah; Tanneberger, Anna; Sader, Robert; Ghanaati, Shahram (Frontiers in Oncology, 2022)
Abstract Introduction: Tumor resection combined with neck dissection (ND) or radiotherapy are established methods for the treatment of patients with oral squamous cell carcinoma (OSCC). However, the extent of ND can lead to postoperative complications. Therefore, for the first time, this study aims to identify lymph node involvement in OSCC performed in a bilateral systematic approach based on oncologic board meetings relying on presurgical magnetic resonance imaging (MRI) and computed tomography (CT). Materials and Methods: In a retrospective single-center study, patients with primary OSCC resection and systematic ND performed in 4 different manners (MRND III bilateral, MRND III left and SND right, MRND III right, SND left, and SND bilateral) were examined. Lymph node involvement allocated to levels was evaluated depending on primary localization and T-stage. Results: A total of 177 consecutive patients (mean age 63.64; 92 female, male 85) were enrolled in this study. A total of 38.98% showed cervical lymph node involvement, and metastases were found in levels 1–4. The distribution of positive lymph node metastases (n=190 LNs) was 39.47% in level 1, 38.95% in level 2, 10.53% in level 3, and 11.05% in level 4. Discussion: In a cohort of OSCC patients with systematic bilateral ND, levels 1 and 2 had positive lymph node involvement, and no lymph node involvement was seen at level 5. Without any clinical or imaging suspicion, ND expanding 5-level MRND should be avoided regardless of the primary tumor localization, T-stage and intraoperative proof of cervical metastases.